Case Report: Retroperitoneal Laparoscopic Partial Nephrectomy for T2 Renal Cell Carcinoma During Pregnancy - Dong, Jie; Zhao, Yi; Xu, Weifeng (Frontiers in Oncology, 2020)
Introduction: Renal cell carcinoma (RCC) found during pregnancy is rare. Treatment strategies and timing of surgeries are controversial. Retroperitoneal laparoscopic partial nephrectomy for T2 RCC during pregnancy has not been reported before. Patient Concerns and Diagnosis: Herein, we report a case of T2 RCC found in a 36-year-old woman during her 21st week of pregnancy. Both ultrasound and magnetic resonance imaging (MRI) suggested a malignancy, possibly renal cell carcinoma. Interventions and Outcomes: After discussion with a multidisciplinary team, the tumor was removed completely via retroperitoneal laparoscopic partial nephrectomy, and pathology result was clear cell RCC. A male infant was delivered full-term uneventful, and both the patient and the boy were in good health after a 46-month follow-up. Conclusion: Partial nephrectomy with retroperitoneal laparoscopic technique is feasible and recommended in some T2 RCC patients.